The Intersection of Statistics and Machine Learning: A Comprehensive Analysis - Hamdoun, Subhi Hammadi; Abed, Mohammed Qadoury; Salman, Salman Mahmood; Al-Bayati, Husam Najm Abbood; Balina, Olena (Journal of Ecohumanism, 2024)
Background: The dynamic interplay between statistics and machine learning has emerged as a focal point in contemporary data science research. As the boundaries between these two disciplines blur, it becomes imperative to explore their intersection and discern the synergies that drive advancements in both fields. Objective: This academic article aims to provide a comprehensive analysis of the intersection between statistics and machine learning, shedding light on the evolving relationship between the two disciplines. The primary objective is to elucidate the key areas where statistical methods and machine learning algorithms converge, offering a nuanced understanding of their complementary roles in extracting meaningful insights from complex datasets. Methods: A systematic literature review was conducted to identify seminal works, methodologies, and applications at the intersection of statistics and machine learning. The selected articles were critically analyzed to distill key themes, methodologies, and trends, providing a comprehensive overview of the current state of this interdisciplinary landscape. Results: Our analysis reveals a rich tapestry of collaborations between statistics and machine learning, ranging from foundational principles to innovative applications. Notably, statistical techniques contribute to the interpretability and generalizability of machine learning models, while machine learning algorithms enhance the predictive power of statistical models in diverse domains. Conclusion: This article concludes by highlighting the symbiotic relationship between statistics and machine learning, emphasizing the need for continued interdisciplinary collaboration. Recognizing the shared principles and leveraging the strengths of both disciplines can pave the way for more robust and interpretable data-driven solutions, fostering advancements in the broader field of data science.Statistics